Correlation Between Serum Concentrations of Menaquinone-4 and Developmental Quotients in Children With Autism Spectrum Disorder - Dong, Hanyu; Wang, Bing; Feng, Junyan; Yue, Xiaojing; Jia, Feiyong (Frontiers in Nutrition, 2021)
Objective: The vitamin K family has a wide range of effects in the body, including the central nervous system. Menaquinone-4 (MK-4), a form of vitamin K2, is converted from phylloquinone (PK), which is the main source of dietary vitamin K and is the main form of vitamin K in the brain. We conducted this study to investigate the serum concentration of MK-4 and the correlations between MK-4 and developmental quotients in children with autism spectrum disorder (ASD). Methods: We selected 731 children with ASD who were diagnosed for the first time. During the same period, 332 neurotypical children who underwent regular physical examinations in our outpatient department were selected as the TD group. We investigated the general situation of children, including gender and age. Children in ASD group were assessed for autistic symptoms and development quotients, including Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), ADOS-2 and Griffiths Development Scales-Chinese Language Edition (GDS-C). Both groups of children were tested for serum menaquinone-4. We compared serum menaquinone-4 levels of ASD group and TD group. We then conducted a correlation analysis between the level of menaquinone-4 and the developmental quotient of children with ASD. Results: The results of this study indicate that the serum concentration of MK-4 in children with ASD is lower than that in children with typical development(t=-2.702, P=0.007). The serum concentration of MK-4 is related to the developmental quotients of several subscales in ASD children, and this correlation is more obvious in males. Conclusion: we conclude that MK-4 is present in lower concentrations in children with ASD, which may affect cognition and developmental quotients. The role of MK-4 in ASD needs to be further explored.